Case report on perioperative management of combined factor V and VIII deficiency in a patient with prolapse uterus - Sree K. P., Bhavani; Rani G., Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Combined factor V and factor VIII deficiency is a rare autosomal recessive disorder with incidence of one in 10,00,000. We reported a case of seventy-one-year-old patient with third degree uterovaginal prolapse, diagnosed as combined factor V and VIII deficiency and the successful perioperative management during vaginal hysterectomy. With our experience in this, we conclude that for the patient's with factor V and VIII deficiency that the correction should be given for at least 2 weeks post operatively.